One perfect spring eaudiobook - Hannon, Irene (Recorded Books Inc., 2014)
Independent single mom Claire Summers is doing her best to make lemonade out of the lemons life has handed her. Workaholic Keith Watson is interested only in the bottom line—until a letter from Claire's eleven-year-old daughter reaches his desk and changes everything. As the executive assistant to a philanthropic businessman, Keith is used to fielding requests for donations. But the girl isn't asking for money. She wants help finding the long-lost son of a neighbor. As Keith reluctantly digs into this assignment in his usual results-oriented style, he has no idea how involved he and Claire will become—nor how unusual the results will actually be. Who could have guessed that a child's kindhearted request would bring love and hope to so many lives ... including his own? Through compelling characters and surprising plot twists, fan favorite Irene Hannon offers this tenderhearted story that demonstrates how life is like lilacs—the biggest blooms come only after the harshest winters.